1981
DOI: 10.1104/pp.68.6.1299
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Glyphosate Inhibition of Carrot Cell Culture Growth by Glycolytic Intermediates and Organic and Amino Acids

Abstract: (12), and carrot (12, 13), tobacco (13), and soybean (12) cell cultures. Gresshoff (12) reported reversal of glyphosate inhibition of Arabidopsis thaliana seedlings with a combination of phenylalanine and tyrosine. In contrast, Duke and Hoagland (6) observed increased inhibition by glyphosate of corn seedling growth when phenylanine and tyrosine were added.Several studies (7,8,16) show that glyphosate treatment can decrease free phenylalanine and tyrosine levels. Recent studies have indicated that glyphosate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Growth (8,9).Coupled with the use ofsuspension cultures, carbon-13 nuclear magnetic resonance (13C NMR) spectroscopy can provide an extremely powerful technique for characterizing metabolic reactions (2, 4, 13). Unlike carbon-14 studies which simply allow the determination of the extent of incorporation of a radiolabel into a given metabolite (after often extensive isolation, separation, and chromatographic purification of the metabolite), the use of specifically '3C-labeled substrates allows the fate of a specific carbon atom to be followed through many enzymic transformations of the original substrate.…”
mentioning
confidence: 99%
“…Growth (8,9).Coupled with the use ofsuspension cultures, carbon-13 nuclear magnetic resonance (13C NMR) spectroscopy can provide an extremely powerful technique for characterizing metabolic reactions (2, 4, 13). Unlike carbon-14 studies which simply allow the determination of the extent of incorporation of a radiolabel into a given metabolite (after often extensive isolation, separation, and chromatographic purification of the metabolite), the use of specifically '3C-labeled substrates allows the fate of a specific carbon atom to be followed through many enzymic transformations of the original substrate.…”
mentioning
confidence: 99%
“…In addition to the previously observed reversal of glyphosate inhibition by aromatic amino acids, it has been reported recently (12) (2), it was concluded that glyphosate may inhibit growth by causing ammonia to increase to toxic levels. Also, the tricarboxylic acid cycle indirectly feeds the shikimic acid pathway, and this cycle could be depleted by the rapid production of shikimic acid in the presence of glyphosate (1).…”
mentioning
confidence: 99%
“…In this paper, we report the effects of aspartate and other reversing agents (12) LSDo.os 9 rose for about 8 h, then leveled off at about 12 cpm iml-' in the presence of aspartate and about 20 cpm-ml-' in the absence of aspartate. Apparently, growth dilution was accompanied by a rapid reduction in net glyphosate uptake, and the longer term glyphosate content of the cells was determined largely during the first 8 h after inoculation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, blockage of the shikimate pathway at EPSPS leads to deregulation of the pathway, resulting in accumulation of huge, possibly phytotoxic, concentrations of shikimate and benzoic acid derivatives of shikimate (Lydon and Duke, 1988). This deregulation and enhanced carbon flow into the shikimate pathway drains other biosynthetic pathways of necessary building blocks (Killmer et al, 1981;Jenson, 1985). Thus, the blockage of the shikimate pathway can lead to a large number of potentially damaging physiological effects.…”
Section: Modes Of Actionmentioning
confidence: 99%